2011
DOI: 10.1111/j.1743-6109.2010.02131.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary Lifelong Delayed Ejaculation: Characteristics and Response to Bupropion

Abstract: Introduction In contrast to premature ejaculation and secondary delayed ejaculation (DE), primary lifelong DE has not been studied extensively. In addition, there is no approved drug treatment. Aims To explore the clinical and laboratory characteristics of a series of men complaining of lifelong DE and to report the response to bupropion. Methods Nineteen con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 36 publications
(52 reference statements)
0
27
1
Order By: Relevance
“…According to the literature, we used the term Delayed Ejaculation (DE) to describe any and all ejaculatory disorders with either a long latency or absence of ejaculation 3 : our sample was composed of 50% of patients with delayed ejaculation and 50% that could not ejaculate. Furthermore, we found that 73.3% of the sample presented lifelong DE: this data is in strong contrast with the literature, where around 25% of patients suffer from lifelong DE, with the remainder reporting it as acquired 7, 27, 28 .…”
Section: Discussioncontrasting
confidence: 99%
“…According to the literature, we used the term Delayed Ejaculation (DE) to describe any and all ejaculatory disorders with either a long latency or absence of ejaculation 3 : our sample was composed of 50% of patients with delayed ejaculation and 50% that could not ejaculate. Furthermore, we found that 73.3% of the sample presented lifelong DE: this data is in strong contrast with the literature, where around 25% of patients suffer from lifelong DE, with the remainder reporting it as acquired 7, 27, 28 .…”
Section: Discussioncontrasting
confidence: 99%
“…Patients with DO have been shown to have higher masturbatory activity, decreased night-time emissions, lower orgasm and intercourse satisfaction scores on the International Index of Erectile Function (IIEF), as well as higher anxiety and depression scores when compared to controls (27). In a study by Xia et al, they compared 24 patients with primary DO and 24 age-matched controls who had no sexual dysfunction complaints (28).…”
Section: Pathophysiologymentioning
confidence: 99%
“…Bupropion (open-label bupropion-SR 150 mg/day for 2 months) was trialed in an age-matched group of 19 males with reported lifelong DO (27). There was a 25% decrease in mean IELT, and the percentage rating control over ejaculation as “fair to good” increased from 0 to 21%.…”
Section: Management Strategies (Figure 2)mentioning
confidence: 99%
“…Rather, induced synchronous activity is a function of multiple factors, including the firing thresholds of individual neurons, with overall excitability tending to be increased with physiological arousal (Maguire & Salpekar, 2013). Indeed, it is notable that different neuropharmacological factors impact thresholds for seizures and sexual climax in similar ways, likely reflecting overall propensity for activation cascades to spread through neuronal networks: thresholds increase with elevated GABA receptor stimulation (Brannon & Rolland, 2000; Calabrò, De Luca, Pollicino, & Bramanti, 2013; Clark & Elliott, 1999), but decrease with elevated glutamate receptor stimulation (Bishop, Chae, Patel, Moline, & Ellingrod, 2012; Crino et al, 2002), dopamine agonists (Andersen & Tufik, 2005; Komisaruk, Beyer-Flores, & Whipple, 2008; Purcell et al, 2013), and dopamine/norepinephrine reuptake inhibitors (Abdel-Hamid & Saleh, 2011; Kim & Steinhart, 2010; Labbate, 1998; Modell, May, & Katholi, 2000). 7…”
Section: Surpassing Thresholds: Variable Impacts Of Rhythms and Variamentioning
confidence: 99%